Deforestation and agricultural fires in South-West Pará, Brazil, under political changes from 2014 to 2020. Issue 1 (31st December 2023) - Jakimow, Benjamin; Baumann, Matthias; Salomão, Caroline; Bendini, Hugo; Hostert, Patrick
ABSTRACT: The increasing deforestation and fires since 2019 raises concerns about the irreversible destruction of the Brazilian Amazon. Our goal was to better understand these changes in south-west Pará across different land-tenure and farm systems and between the terms of President Rousseff, Temer, and Bolsonaro. We reconstructed deforestation and fire history using all Landsat and Sentinel-2 observations from 2014 to 2020 and assessed, using quasi-experimental methods, the average treatment effects of each presidency on deforestation and fires across land-tenure and farm types. Deforestation nearly quadrupled to 1, 201 km 2, particularly during Bolsonaro in undesignated areas and conservation units and on medium-sized farms ( p  < 0.001). Burning increased to 4, 805 km 2 and in all tenure types ( p  < 0.001). The increase was strongest in agrarian settlements and conservation units and on medium and large farms. Our observations show the importance of clarifying land-tenure and re-strengthening disincentives of environmental infractions, which have been weakened specifically under President Bolsonaro.